Understanding brand equity on financial services: a study on the Portuguese banking sector - Rêgo, Miguel Maria Torres Alves de Sousa (2016)
The brand equity subject, although extensively studied for products, has been given little attention in services compared to tangible goods. Thus, it is very pertinent to further explore this concept for service industries so that more valid results can be presented. Due to the nature of services (i.e. for lack of physical attributes people cannot see what there are purchasing) service companies are very dependable on their brands to help them increase the number of customers. For that, to develop a model that assists financial institutions to increase the value of their brands, and additionally to increase the number of customers and sales, reveals to be of extreme utility for modern corporations. The objective of this study is to understand which factors contribute the most for the brand equity creation. The final model combined four independent variables that, based on the literature selected, are expected to have a positive influence on brand equity. A questionnaire was distributed in Portugal, gathering a total of 355 valid responses. From the analysis of the survey, three out of the four variables selected were found to be significant for the brand equity construction. Corporate credibility (CC), perceived value (PV) and brand affinity (BA) help banks to increase reputation, overall perception of quality and emotional connections with their brand, which ultimately increases the value of their brand. The findings also provide readers with some managerial contributions, as well, some limitations and suggestions for future research.